Feeding Limosilactobacillus fermentum K9-2 and Lacticaseibacillus casei K9-1, or Limosilactobacillus reuteri TMW1.656 Reduces Pathogen Load in Weanling Pigs - Wang, Weilan; Zijlstra, Ruurd T.; Gänzle, Michael G. (Frontiers in Microbiology, 2020)
Applying probiotics to improve gut health and growth performance of pigs is considered an effective approach to reduce use of antimicrobial growth promoters in swine production. Understanding the properties of these probiotics is a prerequisite for the selection of probiotic strains for pigs. Host-adapted probiotic strains were suggested to exert probiotic effects by different mechanisms when compared to free-living or nomadic probiotic strains. This study assessed the effect of probiotic intervention with Limosilactobacillus reuteri TMW1.656, a host-adapted species producing the antimicrobial compound reutericyclin, its isogenic and reutericyclin-negative L. reuteri TMW1.656ΔrtcN, and with Limosilactobacillus fermentum and Lacticaseibacillus casei, two species with a nomadic lifestyle. Probiotic strains were supplemented to the post weaning diet in piglets by fermented feed or as freeze-dried cultures. The composition of fecal microbiota was determined by high throughput sequencing of 16S rRNA gene sequence tags; Enterotoxigenic Escherichia coli and Clostridium perfringens were quantified by qPCR targeting specific virulence factors. Inclusion of host-adapted L. reuteri effectively reduced ETEC abundance in swine intestine. In contrast, nomadic L. fermentum and L. casei did not show inhibitory effects on ETEC but reduced the abundance of Clostridium spp.. In addition, the increasing abundance of Bacteriodetes after weaning was correlated to a reduction of ETEC abundance. Remarkably, the early colonization of piglets with ETEC was impacted by maternal-neonatal transmission; the pattern of virulence factors changed significantly over time after weaning. Probiotic intervention or the production of reutericyclin showed limited effect on the overall composition of commensal gut microbiota. In conclusion, the present study provided evidence that the lifestyle of lactobacilli is a relevant criterion for selection of probiotic cultures while the production of antimicrobial compounds has only minor effects.